An analysis of resource sharing scheme in heterogeneous wireless campus network - Masud, M.H.; Abd Latif, Suhaimi; Anwar, Farhat; Hassan Abdalla Hashim, Aisha; Alam, M.K. (2013)
Abstract— The next generation wireless technology systems are being devised with the vision of heterogeneity where a Multimode Device (MD) would be connected with multiple wireless networks like GSM, WiFi, and WiMAX. Bandwidth is one of the main resources of these technologies which is operated independently that need to be aggregated among these technologies in Heterogeneous Wireless Network (HWN). This paper aims to investigate the issues of campus based heterogeneous wireless network, its benefits and challenges. It has been found that an efficient scheduling model for packet reordering and a appropriate interface selection mechanism are important for HWN. Besides its benefits, this paper also addresses the schemes including genetic algorithm, fuzzy logic technique and game theory those have been using for bandwidth allocation. Finally, this paper proposes a mechanism for bandwidth allocation in a HWN environment.